Is there a correlation between creativity and learning achievement? A meta-analysis study - Manaf, Abdul; Dewanti, Sintha Sih; Mam, Socheath; Susetyawati, Endang; Ernawati, Ika (REID (Research and Evaluation in Education), 2022)
This study aims to describe the actual correlation between creativity and learning achievement. The research method used is a meta-analysis involving 41 research titles with 9,675 respondents. This research study involved respondents consisting of elementary education students, secondary education students, and higher education students. The data analysis technique used is a bare-bones meta-analysis. Based on the data analysis, it can be concluded that there is a positive and significant correlation between creativity and learning achievement, both overall and by considering the education level of the respondents. The results of this study recommend that teachers and lecturers develop student creativity in each learning process so that learning outcomes can be optimized.